Studying the effect of electrospark treatment of milk whey on the process of its fermentation and quality of thermoacid cheese - Kochubei-Lytvynenko, Oksana; Chernyushok, Olha; Bilyk, Olena; Bondarenko, Yulia (Eastern-European Journal of Enterprise Technologies, 2019)
The paper reports a study into the influence of electrospark dispersion of current-conductive granules of magnesium and manganese in the environment of milk whey on the process of its fermentation in the technology of making soft thermo-acid cheeses the type of "Adyheyskyy". The object of this study was milk whey, obtained from the thermo-acid settling of cheeses. To prepare the coagulant, it was treated in an electric discharge chamber with a current-conductive layer of magnesium or/and manganese granules manganese over 30...120 s. It has been established that the result of such a treatment of milk whey is the increased magnesium content, by 1.8 to 4 times on average, and the increased manganese content, by 1.5 to 3.8 times on average, depending on the treatment duration. It has been proven that it was characteristic, of all the examined samples, to demonstrate a natural growth of titrated acidity during fermentation. However, the samples enriched with mineral elements following the electrospark treatment over 30...60 s have shown a more intensive growth in titrated acidity. Similar results were obtained when using milk whey from cottage cheese. Although at the initial stages of fermentation (0...6 hours) the increase in acidity was somewhat slower, which has an objective explanation related to the effect of enhanced acidity of the starting whey (50...60 °T) on lactobacilli. It was established that the production cycle is significantly reduced in case of using the proposed technology of acidic whey-coagulant for making thermo-acid cheeses. There is also an increase in the utilization coefficient of technological equipment and its resources. A given technology does not require significant areas for the introduction of an innovative electro-physical technique, and, instead, given the reduced fermentation time, it contributes to reducing the number of containers involved in the preparation of coagulant. It has been established that the use of acidic whey, produced from raw materials enriched with magnesium and manganese, in the technology of thermo-acid cheese contributes to its enrichment with valuable mineral elements. It also provides for a more complete use of the protein potential of milk and, consequently, increases the thermo-acid cheese yield by 1.8...6.5 %